DETERMINAN KECENDERUNGAN KECURANGAN AKUNTANSI DI KOPERASI DALAM PERSPEKTIF FRAUD HEXAGON - Manihuruk, Bunga Sinta Mariani; Nurhayati, Enung; Salta, Salta (Jurnal Riset Keuangan dan Akuntansi, 2024)
The purpose of this study is to analyze the influence of financial pressure, leadership style, effectiveness of internal control, organizational culture, position, and collusion on the tendency of accounting fraud. The population in this study were the administrators of savings and loan service cooperative units in Kuningan Regency, totaling 165 administrators. The sample in this research was 120 cooperatives administrators. The data analysis technique in this research uses Partial Least Square- Structural Equation Modeling (PLS SEM). The results of this research indicate that financial pressure, position, and collusion have a significant positive effect on the tendency of accounting fraud. Meanwhile, leadership, organizational culture and the effectiveness of internal control have a negative effect significant on the tendency of accounting fraud. Keywords: Financial Pressure, Organizational Culture, Position, Collusion, Leadership, Effectiveness of Internal Control, Tendency of Accounting Fraud.